STRATEGI PENGEMBANGAN DESA WISATA RELIGI MAKAM SENTONO DESA GOGODALEM KECAMATAN BRINGIN KABUPATEN SEMARANG - Tri Widodo; Elang Roni Indriyanto (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
This community service aims to describe the Strategy for the Development of Religious Tourism Village, Sentono Tomb, Kauman Hamlet, Gogodalem Village, Bringin Sub-District, Semarang Regency. This place is often used as a place of pilgrimage because there is the tomb of Raden Nitinegoro, a descendant of Sunan Kalijogo. The surrounding community believes that if people often pray at this grave, they will be given blessings in their life. Therefore, this tomb is one of the tourism potentials of Gogodalem Village. However, the tomb's condition seems poorly maintained because it is only cleaned once a week and access to the grave is quite tricky because there is a bridge that pedestrians can only pass, and there are no directions. For this reason, it is necessary to develop by providing adequate cleaning facilities and it is needed to build bridges to make it easier for pilgrims to access the location. The development of tourism information includes introducing tourism objects to outsiders. In addition, to increase tourist visits, Gogodalem Village needs to build a gate right on the side of the road entrance to the Sentono Tomb. The existence of a gate and a clear and easy-to-see identity will attract pilgrims to get to the location of Sentono's Tomb. Besides Makan Sentono, there are some other religious tourist objects in the Gogodalem Village area that potentially become popular.